An inquiry in to meaning and truth - "Russell, Bertrand" (London, 1980)
Russell examines the foundations of knowledge through a discussion of language and investigates the way a knowledge of the structure of language helps our understanding of the structure of the world.
Keywords: "Knowledge, Theory of"